Bone regeneration of mouse critical-sized calvarial defects with human mesenchymal stem cells in scaffold - Im, Jin-Young (Korean Association for Laboratory Animal Science, 2013)
Combination of tissue engineering and cell therapy represents a promising approach for bone regeneration. Human mesenchymal stem cells (hMSCs) have properties that include low immunogenicity, high proliferation rate, and multi-differentiation potential; therefore, they are an attractive seeding source for tissue engineering therapy. Here we found that hMSCs with a scaffold did not affect cell viability and osteogenic differentiation. We also investigated regenerative effect of hMSCs with the scaffold in a calvarial bone defect model. Formation of new bone was evaluated by micro-CT, histology and expression of osteogenic markers. The results clearly showed interesting evidence indicating that hMSCs with scaffold increased the formation of new bone and expression of osteogenic markers, compared to the empty and scaffold only groups. Overall, our results suggest that hMSCs with scaffold are suitable for stimulation of intense bone regeneration in critical-sized bone defects.